AAGAG repeat RNA is an essential component of nuclear matrix in Drosophila. - Pathak, R.U.; Mamillapalli, A.; Rangaraj, N.; Kumar, R.P.; Vasanthi, D.; Mishra, K.; Mishra, R.K. (RNA Biology., 2013)
Eukaryotic nucleus is functionally as well as spatially compartmentalized and maintains dynamic organization of sub-nuclear bodies. This organization is supported by a non-chromatin nuclear structure called the nuclear matrix. Although the precise molecular composition and ultra-structure of the nuclear matrix is not known, proteins and RNA molecules are its major components and several nuclear matrix proteins have been identified. However, the nature of its RNA component is unknown. Here we show that in Drosophila melanogaster, transcripts from AAGAG repeats of several hundred nucleotide in length are critical constituents of the nuclear matrix. While both the strands of this repeat are transcribed and are nuclear matrix associated, the polypurine strand is predominantly detected in situ. We also show that AAGAG RNA is essential for viability. Our results reveal the molecular identity of a critical RNA component of the nuclear architecture and point to one of the utilities of the repetitive part of the genome that has accumulated in higher eukaryotes.